2021
DOI: 10.1111/1475-6773.13708
|View full text |Cite
|
Sign up to set email alerts
|

International comparison of health spending and utilization among people with complex multimorbidity

Abstract: Objective: The objective of this study was to explore cross-country differences in spending and utilization across different domains of care for a multimorbid persona with heart failure and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 14 publications
4
41
0
Order By: Relevance
“…Unlike England, the United States has slightly lower average 30‐day mortality for both personas. While related analyses have shown that the United States is spending more both because of a comparatively higher unit cost and more utilization of postacute care, 16,17 these results suggest that this increased resource use may not be translating into improved long‐term outcomes. Prior work has similarly found that the United States performs above average when it comes to measuring performance related to the period immediately following a hospitalization but then lags behind other countries when assessing longer, population‐level health outcomes 18 .…”
Section: Discussionmentioning
confidence: 93%
“…Unlike England, the United States has slightly lower average 30‐day mortality for both personas. While related analyses have shown that the United States is spending more both because of a comparatively higher unit cost and more utilization of postacute care, 16,17 these results suggest that this increased resource use may not be translating into improved long‐term outcomes. Prior work has similarly found that the United States performs above average when it comes to measuring performance related to the period immediately following a hospitalization but then lags behind other countries when assessing longer, population‐level health outcomes 18 .…”
Section: Discussionmentioning
confidence: 93%
“…One of the key results that emerged from the ICCONIC project was that there is considerable variability across health systems with regards to the relative share of care that occurs in hospitals relative to other care settings. 11 , 12 For example, our findings showed that for both personas, relative hospital utilization in the United States as compared to other countries was low; however, the United States had some of the highest utilization of rehab care days spent outside the hospital in short term rehab and skilled‐nursing facilities. When comparing total utilization, across both care settings, the United States went from being the lowest utilizer to among the highest.…”
Section: Key Lessons From the Icconic Projectmentioning
confidence: 75%
“… 17 For the older adult with multimorbidity, we examined spending of different cohorts of patients to include subsets with limited comorbidity (CHF only) and greater comorbidity (CHF with diagnoses of diabetes and COPD). 12 …”
Section: Key Lessons From the Icconic Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we demonstrate the comparability of these two specific personas—(1) an older adult with frailty who sustains a hip fracture and subsequent hip replacement or osteosynthesis, and (2) an older person with complex multimorbidity, specifically a person hospitalized with heart failure and a comorbidity of diabetes—across the 11 countries in the ICCONIC collaborative. Importantly, this work provides the methodological framework used in an accompanying six original research manuscripts copublished in the Health Services Research “Special Issue on International Comparisons of High Need, High‐Cost Patients.” 9 , 10 , 11 , 12 , 13 , 14 These six original research articles examine detailed variation in spending, utilization, and patient outcomes of the two specific high‐need patient cohorts across different care settings.…”
Section: Introductionmentioning
confidence: 99%